Prediction models for moisture sorption isotherms of soy protein isolate/carboxymethyl chitosan/oleic acid blend films - P. Rachtanapun (2018)
Soy protein isolate/carboxymethyl chitosan/oleic acid (SPI/CMCH/O) blend films were prepared by solution casting. The effect of various oleic acid content (0, 2.5, 5.0, 10.0, 20.0 pph of SPI and CMCH) on water sorption isotherm of SPI/CMCH base film was investigated. The sorption isotherm of SPI/CMCH/O blend films was evaluated at serveral relative humidity (0, 16, 35, 55 and 76% RH), at 25±1°C. The isotherms showed equilibrium moisture content (%EMC) of SPI/CMCH/O blend films decreased when oleic acid content increased. Understanding of sorption isotherms is an importance for prediction of moisture sorption properties of films via moisture sorption empirical models. Guggenheim-Anderson-de Boer (GAB), Brunauer-Emmett-Teller (BET) and Oswin sorption models were tested to fit the experimental data. The root mean squares (RMS) of GAB, BET and Oswin were in the range of 68.60-87.02, 22.86-79.38 and 694.78-3797.23, respectively. BET model was found to be the better-fitted model for SPI/CMCH/O blend films at 25±1°C. © (2012) Trans Tech Publications.